Serum Folate and B12 Levels in Association With Cognitive Impairment Among Seniors: Results From the VELESTINO Study in Greece and Meta-Analysis. (June 2013) - Michelakos, Theodoros; Kousoulis, Antonis A.; Katsiardanis, Konstantinos; Dessypris, Nick; Anastasiou, Anastasia; Katsiardani, Kalliopi-Penelopi; Kanavidis, Prodromos; Stefanadis, Christodoulos; Papadopoulos, Fotios C.; Petridou, Eleni Th.
Objective: To summarize existing evidence on the effect of serum folate and vitamin B12 levels on cognitive impairment among elders via a meta-analysis, also including unpublished data from a cross-sectional study of seniors ( > 65 years) residing in Velestino, Greece.Method: Serum measurements and Mini-Mental State Examination (MMSE) assessments were available for 593 Velestinians. In addition, 12 studies availing data on folate blood levels ( N = 9, 747) and 9 on B12 ( N = 8, 122) were identified following a search algorithm; pooled effect estimates were derived.Results: Cognitive impairment (MMSE < 24) among Velestenians was associated with lower education level in both genders; decreased social activity, depressive symptoms and low folate levels in males; older age in females. Meta-analyses showed an adverse effect of low-folate levels on cognition (OR: 1.66, 95% CI: 1.40-1.96); B12 was nonsignificantly associated (OR: 1.11, 95% CI: 0.88-1.40).Discussion: Low folate levels are associated with cognitive impairment of seniors; underlying pathophysiological mechanisms should be further explored.